2017
DOI: 10.1016/j.stemcr.2017.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Endoglin Is Essential for the Maintenance of Self-Renewal and Chemoresistance in Renal Cancer Stem Cells

Abstract: SummaryRenal cell carcinoma (RCC) is a deadly malignancy due to its tendency to metastasize and resistance to chemotherapy. Stem-like tumor cells often confer these aggressive behaviors. We discovered an endoglin (CD105)-expressing subpopulation in human RCC xenografts and patient samples with a greater capability to form spheres in vitro and tumors in mice at low dilutions than parental cells. Knockdown of CD105 by short hairpin RNA and CRISPR/cas9 reduced stemness markers and sphere-formation ability while a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 59 publications
3
49
0
Order By: Relevance
“…Due to high expression of the CD105 marker, also in our previous study (4%) 12 Caki-1 cell line was used in the present study. As CD105−expressing subpopulation in human RCC xenografts from patient (nephrectomy) samples was shown to possess high capability of self-renewal and ability to form spheres in cell culture in vitro in complement to tumors in mice 28 it remains interesting that CD105− cells also give rise to tumors in our study. It is known that TGFβ pathway activation promote RCC 3D sphere formation and CD105 expression is up-regulated in stem-promoting conditions 33 .…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Due to high expression of the CD105 marker, also in our previous study (4%) 12 Caki-1 cell line was used in the present study. As CD105−expressing subpopulation in human RCC xenografts from patient (nephrectomy) samples was shown to possess high capability of self-renewal and ability to form spheres in cell culture in vitro in complement to tumors in mice 28 it remains interesting that CD105− cells also give rise to tumors in our study. It is known that TGFβ pathway activation promote RCC 3D sphere formation and CD105 expression is up-regulated in stem-promoting conditions 33 .…”
Section: Discussionmentioning
confidence: 85%
“…High CD105 mRNA expression was previously associated with RCC metastases and high tumor stage 29 . In RCC cell lines CD105 www.nature.com/scientificreports www.nature.com/scientificreports/ was reported by us to be highly expressed in metastatic Caki-1 cell line before 12 , as well as by other groups 28 . Moreover, detection of CD105 marker in peripheral blood is considered to be effective tool to evaluate the early metastasis in RCC, especially in a cancer stem cell -positive conditions 30 .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Endoglin (CD105) is a cell membrane glycoprotein overexpressed on proliferating endothelial cells that binds several factors of the TGF-β superfamily, suggesting that activation of this pathway may be responsible for tumor VEGF-independency [46]. In 1995, CD105 was described as a receptor overexpressed in tumor vasculature [47] and, more recently, it has been shown that high CD105 expression on vessels is correlated with poor prognosis in many solid tumors, such as kidney [48], prostate [49], and ovarian cancer [50]. CD105 was also described as a marker of CSC in renal cell carcinoma [16].…”
Section: Alternative Anti-angiogenic Antibodiesmentioning
confidence: 99%
“…Consequently, specific markers such as CD105, ALDH1, CD44, CD133, and CXCR4 have been found in RCC‐derived cancer stem‐like cells . However, a single marker cannot be used for identifying all the CSCs, and therefore, we need to find an appropriate method to discover novel biomarkers and reveal the heterogeneity of CSCs. This can help in clarifying the role of CSCs in the occurrence, development, recurrence, metastasis, and multidrug resistance of renal tumors and can enable more personalized treatment strategies to establish novel therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%